A heterogeneous model integration and interoperation approach in distributed collaborative simulation environment. Issue 3 (6th July 2010) - Fan, Miaomiao; Zhang, Jianliang; Fan, Yushun
The integration and interoperation among heterogeneous distributed models is an important technique to realise distributed collaborative simulation for complex product development. HLA and web service technology are employed to facilitate the integration in this paper. First, the HLA-enabling method based on HLA agent model is proposed to make models created through commercial software conforming to HLA standard. In order to make up the drawbacks of HLA based simulation in interoperability on the WAN, a collaborative simulation framework by combining HLA with web service merits is proposed and described in details. Finally, a prototype system for heterogeneous models integration in forging manipulator system is implemented, where a method of developing ABAQUS engine agent is present, which could solve the difficulty of wrapping ABAQUS software. The case study verifies the high fidelity and effectiveness of our integration and interoperation approach.